Dyspnea due to Pulmonary Vessel Arteritis - Suzana M Gilmour; Giulio S Dominelli; Jonathon A Leipsic; Robert D Levy (Canadian Respiratory Journal)
Pulmonary arteritis is a rare cause of pulmonary hypertension. Causes of pulmonary arteritis can be divided into primary and secondary, as well as classified according to vessel size. Only large vessel vasculitis is associated with pulmonary hypertension; primary forms include Takayasu arteritis and giant cell arteritis. The diagnosis of pulmonary arteritis can be challenging and the associated morbidity is serious without prompt, directed treatment. The authors present a case involving a 48-year-old First Nations man presenting with a six-month history of exertional dyspnea and severe stenosis of the left pulmonary artery, who was ultimately diagnosed with pulmonary arteritis related to large vessel vasculitis.